2016
DOI: 10.1534/g3.116.028951
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Mosaic Screen Reveals Ecdysone-Responsive Genes RegulatingDrosophilaOogenesis

Abstract: Multiple aspects of Drosophila oogenesis, including germline stem cell activity, germ cell differentiation, and follicle survival, are regulated by the steroid hormone ecdysone. While the transcriptional targets of ecdysone signaling during development have been studied extensively, targets in the ovary remain largely unknown. Early studies of salivary gland polytene chromosomes led to a model in which ecdysone stimulates a hierarchical transcriptional cascade, wherein a core group of ecdysone-sensitive transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 95 publications
(152 reference statements)
1
45
0
Order By: Relevance
“…Prior studies had demonstrated that the transcriptional regulators EcR and Tai are required in border cells after motile cell specification occurs through JAK/STAT/Slbo activation(Bai et al, 2000; Cherbas et al, 2003; Hackney et al, 2007; Jang et al, 2009). A role for transcriptional regulation during cell migration is underappreciated, aside from the transcriptional programs required for cell fate, possibly because many cell migration events have been studied in vitro and signaling regulation on the protein level is often sufficient for accurate movements (Ables et al, 2016; Riddiford et al, 1993). In vivo, however, transcriptional control adds a layer of adaptability in responding to environmental and growth cues, so it is likely to be essential within migrating cells during development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies had demonstrated that the transcriptional regulators EcR and Tai are required in border cells after motile cell specification occurs through JAK/STAT/Slbo activation(Bai et al, 2000; Cherbas et al, 2003; Hackney et al, 2007; Jang et al, 2009). A role for transcriptional regulation during cell migration is underappreciated, aside from the transcriptional programs required for cell fate, possibly because many cell migration events have been studied in vitro and signaling regulation on the protein level is often sufficient for accurate movements (Ables et al, 2016; Riddiford et al, 1993). In vivo, however, transcriptional control adds a layer of adaptability in responding to environmental and growth cues, so it is likely to be essential within migrating cells during development.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, early expression of an activated form of tai ( taiΔB ) can cause abnormally early movements of the border cell cluster, but only in combination with ectopically early specification via STAT activation (Jang et al, 2009). Several key ecdysone targets have been identified during metamorphosis (Beckstead et al, 2005; Beckstead et al, 2007), and in ovary (Ables et al, 2015; Ables and Drummond-Barbosa, 2010; Ables et al, 2016; Buszczak et al, 1999; Terashima and Bownes, 2005), but few are known to have roles in cell motility. Furthermore, it is not clear how downstream targets for EcR, Tai, STAT, and Slbo coordinate their activities to result in proper temporal control of border cell movements.…”
Section: Introductionmentioning
confidence: 99%
“…Ecdysone signaling mediates the increase in GSC proliferation induced by the first mating of young females [26], and is necessary for sustained GSC proliferation and self-renewal [38]. Ecdysone signaling is also necessary for the differentiation of germ cells and the individualization of germline cysts into discrete follicles [39, 23, 40, 41]. As oogenesis proceeds, ecdysone signaling is required for the growth and survival of germline cysts at two important developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic screen designed to find ecdysone-responsive genes required for oogenesis identified several genes that modulate the fate and proliferative capacity of FSCs [41]. FSCs give rise to the follicle cell lineage, which is required for proper germline development and ultimately forms the eggshell [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation